2016
DOI: 10.1177/1948550616628608
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Look on Money Priming

Abstract: Two studies demonstrated that subjective socioeconomic status moderates the effects of reminders of money on the endorsement of the socioeconomic system. Whether reminders of money increased or decreased system justification (Study 1) and the belief in a just world (Study 2) depended on participants’ subjectively experienced standing in the social hierarchy. These findings were backed up by a small-scale meta-analysis across our entire data (N = 365). Hence, we also included a third study into the meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The cumulative analysis on the direct measures seems to provide some tentative support for the interaction hypothesis. In contrast to the main effect hypothesis and in line with previous research (Schuler & Wänke, 2016), the cumulative evidence revealed a marginally significant effect for the moderation hypothesis. However, the effect did not reach conventional levels of significance (p < .05) and should be interpreted with caution.…”
Section: The Interaction-effect Hypothesissupporting
confidence: 83%
See 4 more Smart Citations
“…The cumulative analysis on the direct measures seems to provide some tentative support for the interaction hypothesis. In contrast to the main effect hypothesis and in line with previous research (Schuler & Wänke, 2016), the cumulative evidence revealed a marginally significant effect for the moderation hypothesis. However, the effect did not reach conventional levels of significance (p < .05) and should be interpreted with caution.…”
Section: The Interaction-effect Hypothesissupporting
confidence: 83%
“…Empirical support for the theoretical claim that money priming makes people more focused on themselves and their personal benefits has been shown across different countries and cultural backgrounds (Vohs, 2015). Furthermore, Schuler and Wänke (2016) tested U.S.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations